2014
DOI: 10.1111/chd.12166
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma B-type Natriuretic Peptide and C-reactive Protein Levels in Children with Restrictive Right Ventricular Physiology Following Tetralogy of Fallot Repair

Abstract: rRV physiology is associated with significantly higher BNP and CRP levels with poorer balance of systemic oxygen transport. Information about these pathophysiological changes may help to identify appropriate treatment strategies in this difficult group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…[157][158][159]163,165 BNP in tetralogy of Fallot The clinical relevance of BNP in the integrated followup of patients after tetralogy of Fallot repair has been assessed in several studies. [167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186] Patients after tetralogy of Fallot correction can demonstrate a series of typical pathological sequelae, such as residual pulmonary regurgitation and/or stenosis, causing right ventricular dilatation, hypertrophy, or both. Patients with these cardiac alterations may be initially asymptomatic, but subsequently deteriorate progressively into having symptomatic heart failure.…”
Section: Bnp In the Follow-up Of Corrected/palliated Chdmentioning
confidence: 99%
See 2 more Smart Citations
“…[157][158][159]163,165 BNP in tetralogy of Fallot The clinical relevance of BNP in the integrated followup of patients after tetralogy of Fallot repair has been assessed in several studies. [167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186] Patients after tetralogy of Fallot correction can demonstrate a series of typical pathological sequelae, such as residual pulmonary regurgitation and/or stenosis, causing right ventricular dilatation, hypertrophy, or both. Patients with these cardiac alterations may be initially asymptomatic, but subsequently deteriorate progressively into having symptomatic heart failure.…”
Section: Bnp In the Follow-up Of Corrected/palliated Chdmentioning
confidence: 99%
“…167,168 At present, there are no solid guidelines for the management of these patients, in particular concerning the critical values of elevated right ventricular dimensions to take into account for an eventual re-intervention. [167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183][184][185][186] The use of BNP may provide important additional information both for the evaluation of asymptomatic individuals as well to grade and monitor the degree of heart failure. [8][9][10] In the last decade, a large number of studies have reported significant relationships between circulating levels of biomarkers and several structural and functional parameters as assessed by echocardiography and MRI.…”
Section: Bnp In the Follow-up Of Corrected/palliated Chdmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Child A it may be that early extubation was in her best interests. A late complete tetralogy of Fallot repair in an older child may result in the occurrence of restrictive right ventricular physiology during the initial post-operative period more frequently than if the repair is completed electively during infancy due to ventricular hypertrophy and fibrosis (32). If clinically significant, left ventricular filling may also be indirectly affected (33).…”
Section: Discussionmentioning
confidence: 99%
“…Further, oxygen transport between patients with restrictive right ventricle and those without right ventricle decides CHD in children [13] Serum kinetics in children is also used to identify atrial and ventricular septal defects closure in terms of extracorporeal circulation. C-reactive protein demonstrates functional status of cardiac muscle functional status.…”
Section: Physiological Markersmentioning
confidence: 99%